Can patriarchal attitudes moderate the relation between women on boards and firm economic performance? - Paula Castro; María T. Tascón; Sara Corral (European Research on Management and Business Economics, 2023)
The paper investigates the moderating effect of patriarchal attitudes by country and year on the relationship between gender diversity on boards and firm performance. The international sample analyzed is composed of 1,103 listed firms from 18 European countries for the period of 2005–2019. Using a two-step system GMM approach, the analysis shows how the generally positive relationship between gender diversity and economic performance (proxied by return on assets and Tobin's Q) is offset and even surpassed by the negative moderating effect of patriarchal attitudes. Furthermore, our work tests critical mass theory and finds confirmation in line with the results obtained for gender diversity. The main contributions of this work include its use of new specific proxies for gender culture by country, namely, patriarchal attitudes and the finding of how they affect the relationship between women's board participation and firm performance in a negative and consistent way.